High-strength metal-ceramic composite material and preparation method thereof

Through ultrasonic vibration ball milling, pulsed electromagnetic field hot pressing forming, carbon nanotube addition and spark plasma sintering technology, the problem of traditional composite materials being easily delaminated or broken when external forces are applied is solved, and the strength and toughness of the composite materials are significantly improved.

CN119426601AInactive Publication Date: 2025-02-14BEIJING PENGYUAN NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411626851.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional metal and ceramic composite materials are prone to delamination or fracture when external forces are applied, and high sintering temperature leads to deformation or decomposition of ceramic phases, and low density affects mechanical properties.

Method used

Ultrasonic vibration-assisted ball milling treatment improves powder dispersion and interface bonding force, introduces pulsed electromagnetic fields for hot-pressing, adds surface-treated carbon nanotubes, and uses spark plasma sintering technology to sinter in an inert atmosphere.

Benefits of technology

It significantly enhances the interface bonding force between metal and ceramics, improves the overall performance and density of composite materials, avoids deformation or decomposition of ceramic phases at high temperatures, and realizes high-strength and high-toughness composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426601A_ABST
    Figure CN119426601A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses a high-strength metal-ceramic composite material and a preparation method thereof, and the preparation method comprises the following steps: (a) mixing selected metal powder and ceramic powder according to a specific proportion to form a uniform mixture; (b) carrying out ultrasonic vibration assisted ball milling treatment on the mixture, wherein the ball milling time is 2-4 hours; (c) applying pressure to the mixture in an inert atmosphere, heating, and carrying out hot press molding for 2 hours; (d) adding a carbon nanotube subjected to surface treatment into the mixture as a nanoparticle reinforcement phase; through surface modification of the metal powder and addition of the carbon nanotubes, the interface bonding force between metal and ceramic is remarkably enhanced, the overall performance of the composite material is improved, ultrasonic vibration is adopted to assist ball milling treatment, the dispersity of the powder is improved, and the mixing uniformity is improved, so that the temperature required by sintering is reduced, and the service life of the composite material is prolonged. And deformation or decomposition of the ceramic phase at high temperature is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a high-strength metal-ceramic composite material and a preparation method thereof. Background Art

[0002] Composite materials are new materials composed of two or more materials with different properties. The properties of the component materials are optimized to obtain comprehensive properties that cannot be achieved by a single material. Metal-ceramic composites are widely used in aerospace, automobile manufacturing, medical devices and other fields due to their unique properties. Such composites usually have high hardness, wear resistance, corrosion resistance and good mechanical properties. However, the interface bonding between metal and ceramic in traditional preparation methods is weak, which makes the composite material prone to delamination or fracture when subjected to external forces. And because the sintering temperature difference between metal and ceramic is large, the traditional process requires a higher sintering temperature, which may cause deformation or decomposition of the ceramic phase, thereby affecting the overall performance of the composite material. At the same time, it is difficult for traditional molding methods to completely eliminate pores, resulting in a low density of the composite material, affecting its mechanical properties. Summary of the invention

[0003] The object of the present invention is to provide a high-strength metal-ceramic composite material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] To achieve the above object, the present invention provides the following technical solutions: A high-strength metal-ceramic composite material and a preparation method thereof, comprising the steps of: (a) mixing selected metal powder and ceramic powder in a specific ratio to form a uniform mixture; (b) subjecting the mixture to ultrasonic vibration-assisted ball milling treatment to improve the dispersibility of the powder, increase the mixing uniformity and reduce the sintering temperature, the ball milling time being 2-4 hours; (c) applying pressure and heating to the mixture in an inert atmosphere for 2 hours to perform hot pressing, and introducing a pulsed electromagnetic field during the hot pressing process to promote densification between particles inside the material and improve the microstructure of the material; (d) adding surface-treated carbon nanotubes as nanoparticle reinforcement phase to the mixture, wherein the amount of the carbon nanotubes added is 1% of the total mass of the mixture, and the carbon nanotubes are pre-treated with chemical nickel plating and coated with a surfactant to enhance compatibility and interfacial bonding with metal and ceramic substrates; (e) sintering the formed sample by spark plasma sintering technology, wherein the sintering process is carried out in an inert atmosphere for 45 minutes; The spark plasma sintering temperature is higher than the melting point of the metal powder but lower than the melting point of the ceramic powder. The sintering temperature is 1250-1300° C., which can achieve good interface bonding without destroying the ceramic phase.

[0005] Preferably, the metal powder is surface-modified by a chemical vapor deposition (CVD) process to improve the interfacial bonding strength between the metal powder and the ceramic powder.

[0006] Preferably, the ratio of the metal powder to the ceramic powder is 1.5:1 (weight ratio), which enables the composite material to achieve an optimal balance in mechanical properties.

[0007] Preferably, the composite material has a tensile strength greater than 1.2 GPa and a fracture toughness greater than 12 MPa·m^(1 / 2), and is suitable for structural components in high temperature and high pressure environments in the aerospace industry.

[0008] Preferably, during the ball milling process of step (b), a small amount of surfactant is added to reduce powder agglomeration and improve the dispersibility of the powder, and a drying process is performed after ball milling to remove the residual surfactant.

[0009] Preferably, the pressure range of the hot pressing molding is 180-220 MPa, and the temperature range is 1000-1100° C. The hot pressing molding under the above conditions can significantly improve the density and uniformity of the microstructure of the composite material.

[0010] Preferably, during the hot pressing process of step (c), a gradient temperature increase is adopted, that is, the temperature is slowly increased from room temperature to the hot pressing temperature range, so as to reduce thermal stress and improve the microstructure uniformity and density of the material.

[0011] Preferably, after the spark plasma sintering in step (e), an annealing treatment is performed to eliminate internal stress and optimize the microstructure, wherein the annealing treatment is performed in an inert atmosphere at a temperature range of 1000-1100° C. for 1-2 hours.

[0012] Preferably, the metal powder is selected from one of the titanium alloys, and the ceramic powder is selected from one of the aluminum oxides.

[0013] Furthermore, the present invention provides a high-strength metal-ceramic composite material, which is prepared by the above preparation method.

[0014] The present invention has at least the following beneficial effects: (1) This scheme significantly enhances the interfacial bonding between metal and ceramic by surface modification of metal powder and addition of carbon nanotubes, improves the overall performance of the composite material, and uses ultrasonic vibration-assisted ball milling to improve the dispersion of the powder and the uniformity of mixing, thereby reducing the temperature required for sintering and avoiding deformation or decomposition of the ceramic phase at high temperatures. The use of ultrasonic vibration-assisted ball milling effectively reduces powder agglomeration, improves the dispersion of the powder, and makes the microstructure of the composite material more uniform.

[0015] (2) This scheme introduces a pulsed electromagnetic field during the hot pressing process, which promotes the densification between particles inside the material and improves the density of the composite material.

[0016] (3) This scheme optimizes the microstructure of the composite material and improves its comprehensive performance through a gradient heating hot pressing process and subsequent annealing treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0018] Figure 1 It is a schematic diagram of the preparation method of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 See also Figure 1 The present invention provides a technical solution: a high-strength metal-ceramic composite material and a preparation method thereof, the preparation steps are as follows: Raw materials preparation: Ti-6Al-4V titanium alloy powder was selected as the metal phase, with a particle size of 5-15 μm; α-Al2O3 alumina powder is selected as the ceramic phase, with a particle size of 1-3 μm; The selection of Ti-6Al-4V titanium alloy powder and α-Al2O3 alumina powder ensures that the composite material has good mechanical properties, and the small particle size of the powder helps to form a more uniform microstructure.

[0021] Carbon nanotubes treated with chemical nickel plating are selected as the nanoparticle reinforcement phase.

[0022] Powder Mixing: Mix the two powders in a weight ratio of 1.5:1 between metal powder and ceramic powder; Stearic acid is added as a surfactant to reduce powder agglomeration and improve dispersibility; The treatment was carried out using an ultrasonic vibration-assisted ball mill, and the ball milling time was 3 hours.

[0023] Thermoforming: In an argon atmosphere, the dried mixed powder is loaded into a mold; A pressure of 200 MPa was applied on the hot press, and the temperature was gradually increased from room temperature to 1050 °C in a gradient manner for 2 h; A pulsed electromagnetic field is introduced during the hot pressing process.

[0024] The application of pulsed electromagnetic fields can improve the microstructure inside the material and promote material densification. Gradient heating helps to avoid defects caused by sudden temperature changes.

[0025] Adding carbon nanotubes: 1% carbon nanotubes by weight were added to the mixture. The carbon nanotubes were previously treated with chemical nickel plating and coated with stearic acid.

[0026] The addition of carbon nanotubes further enhances the mechanical properties of the composite material. Carbon nanotubes treated with chemical nickel plating and coated with stearic acid can effectively improve the strength and toughness of the composite material.

[0027] Spark plasma sintering: The hot-pressed samples were placed in the SPS equipment, and the sintering temperature was set to 1275°C for 45 minutes; Ensure that the sintering process is carried out in an inert atmosphere.

[0028] Spark plasma sintering can achieve rapid sintering in a short time, improve density and microstructure control accuracy. Sintering in an inert atmosphere can prevent unnecessary reactions or oxidation of materials at high temperatures, ensuring the quality of the materials.

[0029] Annealing treatment: After spark plasma sintering, the sample was annealed at 1050°C for 1.5 hours to eliminate internal stress and improve the microstructure of the material, thereby improving the stability and reliability of the material and making it more suitable for practical applications.

[0030] Performance Test: Mechanical property tests, including tensile strength and fracture toughness, were performed to verify whether the composite material met the expected targets, i.e., tensile strength greater than 1.2 GPa and fracture toughness greater than 12 MPa·m^(1 / 2).

[0031] Example 2 The present invention also protects a technical solution: a high-strength metal-ceramic composite material and a preparation method thereof, the preparation steps are as follows: Preparation steps: Raw materials preparation: Ti-6Al-4V titanium alloy powder was selected as the metal phase, with a particle size of 5-15 μm; α-Al2O3 alumina powder is selected as the ceramic phase, with a particle size of 1-3 μm; Carbon nanotubes treated with chemical nickel plating are selected as the nanoparticle reinforcement phase.

[0032] Metal powder surface modification: The surface of titanium alloy powder is modified by chemical vapor deposition (CVD) process to improve the interfacial bonding between metal powder and ceramic powder. The bonding state between different phases inside the composite material is improved, thereby enhancing the overall performance of the material.

[0033] Powder Mixing: Mix the two powders in a weight ratio of 1.5:1 between metal powder and ceramic powder; Stearic acid is added as a surfactant to reduce powder agglomeration and improve dispersibility; The treatment was carried out using an ultrasonic vibration-assisted ball mill, and the ball milling time was 3 hours.

[0034] Thermoforming: In an argon atmosphere, the dried mixed powder is loaded into a mold; A pressure of 200 MPa was applied on the hot press, and the temperature was gradually increased from room temperature to 1050 °C in a gradient manner for 2 h; A pulsed electromagnetic field is introduced during the hot pressing process.

[0035] Adding carbon nanotubes: 1% carbon nanotubes by weight were added to the mixture. The carbon nanotubes were previously treated with chemical nickel plating and coated with stearic acid.

[0036] Spark plasma sintering: The hot-pressed samples were placed in the SPS equipment, and the sintering temperature was set to 1275°C for 45 minutes; Ensure that the sintering process is carried out in an inert atmosphere.

[0037] Annealing treatment: After spark plasma sintering, the samples were annealed at 1050 °C for 1.5 h.

[0038] Performance Testing Mechanical property tests, including tensile strength and fracture toughness, were performed to verify whether the composite material met the expected targets, i.e., tensile strength greater than 1.2 GPa and fracture toughness greater than 12 MPa·m^(1 / 2).

[0039] Example 3 The present invention also protects a technical solution: a high-strength metal-ceramic composite material and a preparation method thereof, the preparation steps are as follows: Raw materials preparation: Ti-6Al-4V titanium alloy powder was selected as the metal phase, with a particle size of 5-15 μm; α-Al2O3 alumina powder is selected as the ceramic phase, with a particle size of 1-3 μm; Carbon nanotubes treated with chemical nickel plating are selected as the nanoparticle reinforcement phase.

[0040] Powder Mixing: Mix the two powders in a weight ratio of 1.5:1 between metal powder and ceramic powder; Stearic acid is added as a surfactant to reduce powder agglomeration and improve dispersibility; The treatment was carried out using an ultrasonic vibration-assisted ball mill, and the ball milling time was 3 hours.

[0041] Thermoforming: In an argon atmosphere, the dried mixed powder is loaded into a mold; A pressure of 210 MPa was applied on the hot press, and the temperature was gradually increased from room temperature to 1075 °C in a gradient manner for 2 h; A pulsed electromagnetic field is introduced during the hot pressing process.

[0042] Adding carbon nanotubes: 1% carbon nanotubes by weight were added to the mixture. The carbon nanotubes were previously treated with chemical nickel plating and coated with stearic acid.

[0043] Spark plasma sintering: The hot-pressed samples were placed in the SPS equipment, and the sintering temperature was set to 1275°C for 45 minutes; Ensure that the sintering process is carried out in an inert atmosphere.

[0044] Annealing treatment: After spark plasma sintering, the samples were annealed at 1050 °C for 1.5 h.

[0045] Performance Testing Mechanical property tests, including tensile strength and fracture toughness, were performed to verify whether the composite material met the expected targets, i.e., tensile strength greater than 1.2 GPa and fracture toughness greater than 12 MPa·m^(1 / 2).

[0046] Comparative Example 1 This embodiment provides the preparation of a composite material without adding carbon nanotubes The preparation steps are as follows: Raw materials preparation: Ti-6Al-4V titanium alloy powder was selected as the metal phase, with a particle size of 5-15 μm; α-Al2O3 alumina powder is selected as the ceramic phase, and the particle size is 1-3 μm.

[0047] Powder Mixing: Mix the two powders in a weight ratio of 1.5:1 between metal powder and ceramic powder; Stearic acid is added as a surfactant to reduce powder agglomeration and improve dispersibility; The treatment was carried out using an ultrasonic vibration-assisted ball mill, and the ball milling time was 3 hours.

[0048] Thermoforming: In an argon atmosphere, the dried mixed powder is loaded into a mold; A pressure of 200 MPa was applied on the hot press, and the temperature was gradually increased from room temperature to 1050 °C in a gradient manner for 2 h; A pulsed electromagnetic field is introduced during the hot pressing process.

[0049] Spark plasma sintering: The hot-pressed samples were placed in the SPS equipment, and the sintering temperature was set to 1275°C for 45 minutes; Ensure that the sintering process is carried out in an inert atmosphere.

[0050] Annealing treatment: After spark plasma sintering, the samples were annealed at 1050 °C for 1.5 h.

[0051] Performance Testing Mechanical property tests, including tensile strength and fracture toughness, were performed to verify whether the composite material met the expected targets, i.e., tensile strength greater than 1.2 GPa and fracture toughness greater than 12 MPa·m^(1 / 2).

[0052] In summary, the effects of the embodiments of the present invention and the comparative examples are as follows: Example 1 represents a preparation method under standard conditions, aiming at achieving a high performance composite material.

[0053] Example 2 improves the interfacial bonding strength between metal and ceramic by CVD surface modification of metal powder, which is expected to bring better mechanical properties.

[0054] Example 3 explores the effect of different hot pressing conditions on the properties of the composite material by adjusting the hot pressing conditions (higher pressure and temperature).

[0055] Comparative Example 1 does not add carbon nanotubes, and is used to compare the effects of carbon nanotubes on the properties of the composite material.

[0056] Comparative Example 2 does not use ultrasonic vibration-assisted ball milling, but aims to study the effect of ultrasonic vibration-assisted ball milling on powder dispersibility and mixing uniformity.

[0057] Example 1 provides a baseline, demonstrating the method of preparing a composite material under standard conditions.

[0058] In Example 2, the interfacial bonding force between metal and ceramic is enhanced by surface modification of metal powder, which is expected to improve the overall performance of the composite material.

[0059] Example 3 explores the effect of adjusting the hot pressing conditions on the properties of the composite material, which may help to further optimize the microstructure of the material.

[0060] Comparative Examples 1 and 2, respectively, removed the carbon nanotube addition and ultrasonic vibration-assisted ball milling treatment, in order to evaluate the contribution of these steps to the properties of the composites.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-strength metal-ceramic composite material, characterized in that: Includes steps: (a) mixing selected metal powder and ceramic powder in a specific ratio to form a uniform mixture; (b) subjecting the mixture to ultrasonic vibration-assisted ball milling for 2-4 hours; (c) applying pressure and heating to the mixture in an inert atmosphere for 2 hours to perform hot pressing, and introducing a pulsed electromagnetic field during the hot pressing process; (d) adding surface-treated carbon nanotubes as nanoparticle reinforcement phase to the mixture, wherein the amount of the carbon nanotubes added is 1% of the total mass of the mixture, the carbon nanotubes are pre-treated with chemical nickel plating, and are coated with a surfactant; (e) sintering the formed sample by spark plasma sintering technology, wherein the sintering process is carried out in an inert atmosphere for 45 minutes; The spark plasma sintering temperature is higher than the melting point of the metal powder but lower than the melting point of the ceramic powder, and the sintering temperature is 1250-1300°C.

2. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: The metal powder is surface modified by a chemical vapor deposition (CVD) process.

3. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: The ratio of the metal powder to the ceramic powder is 1.5:1 (weight ratio), which enables the composite material to achieve an optimal balance of mechanical properties.

4. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: The composite material has a tensile strength greater than 1.2 GPa and a fracture toughness greater than 12 MPa·m^(1 / 2).

5. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: During the ball milling process of step (b), a small amount of surfactant is added to reduce powder agglomeration, and a drying process is performed after ball milling to remove the residual surfactant.

6. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: The pressure range of the hot pressing molding is 180-220 MPa, and the temperature range is 1000-1100°C.

7. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: During the hot pressing process of step (c), a gradient heating method is adopted, that is, the temperature is slowly raised from room temperature to the hot pressing temperature range.

8. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: After the spark plasma sintering in step (e), an annealing treatment is performed in an inert atmosphere at a temperature range of 1000-1100° C. for 1-2 hours.

9. The method for preparing a high-strength metal-ceramic composite material according to claim 1, characterized in that: The metal powder is selected from one of the titanium alloys, and the ceramic powder is selected from one of the aluminum oxides.

10. A high-strength metal-ceramic composite material, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Cited By

  • High-hardness and high-wear-resistance metal-based ceramic particle in-situ reinforced composite material and preparation method thereof

    CN120205816A